2019
DOI: 10.1021/acs.jpcc.9b04451
|View full text |Cite
|
Sign up to set email alerts
|

Precursor Structures for Polymorphic Titanyl Phthalocyanine Crystal Phases on Au(111): A High-Resolution STM Study

Abstract: The adsorption, assembly, and growth mechanism of the optoelectronic titanyl phthalocyanine (TiOPc) molecules on Au(111) were carefully investigated by low-temperature and highresolution scanning tunneling microscopy (STM). Three domains, i.e., Y, I, and II, were formed on Au(111) with its coverage increased up to six monolayers (MLs), as structurally scrutinized at the submolecular level. The TiOPc molecules were adsorbed with their Pc planes parallel to the substrate surface in domains Y and I, while the Pc … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 43 publications
6
17
0
1
Order By: Relevance
“…Figure 2) and looks similar to that observed by Zhu et al, which they denoted as domain B. 22 We can confirm, that this phase appears to be thermally metastable, as it disappears upon annealing at 420− 450 K, yielding again the long-range ordered film structure that resembles those prepared at 450 K.…”
Section: Morphology and Crystallinesupporting
confidence: 87%
See 3 more Smart Citations
“…Figure 2) and looks similar to that observed by Zhu et al, which they denoted as domain B. 22 We can confirm, that this phase appears to be thermally metastable, as it disappears upon annealing at 420− 450 K, yielding again the long-range ordered film structure that resembles those prepared at 450 K.…”
Section: Morphology and Crystallinesupporting
confidence: 87%
“…31 Using STM, Zhu et al reported a particular phase for TiOPc bilayer films at RT on Au(111), characterized by a molecular inclination of 30°according to their analysis. 22 Since such a structure could not be confirmed by our results and appears quite unusual; we reexamined their data. Using proper values for the van-der-Waals dimensions of the molecular size (instead of distances between diametrical carbon ring centers), we found significant inconsistency in their analysis (see Figure S9), which challenges their interpretation.…”
Section: Morphology and Crystallinementioning
confidence: 79%
See 2 more Smart Citations
“…Construction of two-dimensional (2D) structures on surfaces has attracted great attention due to their unique properties and robust preparation methodology. Most 2D materials can be achieved by short-range interactions which typically function within a short distance of less than 5 Å, including covalent bonds, ionic bonds, halogen bonds, hydrogen bonds, dispersion force, metal-coordinated interaction, and organic-ionic compound interaction . Among all these interactions, the dispersion force is very weak and decreases rapidly with separation which is therefore taken as a short-range interaction on the surface.…”
mentioning
confidence: 99%